Pengembangan Pola Berpikir Sistematis Melalui Pengenalan Pemrograman Visual Pada Peserta didik Tingkat Menengah Atas - Robby Tan; Maresha Caroline Wijanto; Oscar Karnalim; Setia Budi; Mewati Ayub; Diana Trivena Yulianti; Hendra Bunyamin; Sendy Ferdian Sujadi; Rossevine Artha Natasya (University of Muhammadiyah Malang, 2021)
Systematic thinking is a process of thinking that should be introduced from early age. While developing such thinking, students will learn how to solve a task by breaking it down to smaller tasks and complete them one by one. There are many activities that can support such thinking. One of them is to program visually. Visual programming is usually featured with drop-down blocks where students are only required to choose which process or logic needed than then put them in the play board. A training of such activity was done in a high school at Bandung, Indonesia with Scratch. Students were first introduced with Scratch, a software that is expected to help them think systematically. For conducting the training itself, several stages were followed. It started with introduction, and then followed by lecture and case-based practice. To engage students with the practice, the case study is COVID-19 where students are expected to deliver relevant information creatively, such as developing a game of social distancing, spray vs virus, etc. Evaluation shows that via this training, students were able to further develop their own systematic thinking via the creation of Scratch projects. Further, they believed that this training is interesting and can help them to study in the high school.